Formulating Oil Palm Investment Decision in Tidal Wetlands of South Sumatra, Indonesia - Elisa Wildayana (Journal of Wetlands Environmental Management, 2014)
The research aimed to formulate an investment decision for oil palm plantation in tidal wetlands of PulauRimau, Banyuasin South Sumatra Indonesia. The research summarized that Land productivity and input amount will determine some differences of each soil suitability (S1, S2 and S3). The more land suitability level is, the more Fresh Fruit Bunches of Oil Palm (FFB) productivity per ha is produced and the less input is given.Â  Net B/C Ratio, NPV and IRR for all land suitability classes are financially feasible for oil palm plantation development, however the most feasible and the most Expected Rate of Return (IRR) is in tidal wetlands with S1 land suitability (very suitable), followed by S2 (suitable) and S3 (marginally suitable). Sensitivity analysis to feasibility for three land suitability is still economically feasible to build and to develop oil palm plantation, especially in large scale, thus its decision for capital investment is suitable.